(3OhGhjf GdTYQGA GdSJI GdLGgdjfs - (3eLehYI TYQGAs
(3ChdgG (B:s
(3bGd (B((3GeQD GdbjS(B): (3baG fHc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3ef TYQ YfJQI bhdg(B: (3hcGf aJi GdgjLGA jMej PeGQgG hjVQH YfO GdcQ cd HfGf s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3hGdhQbI GdChdi hGdCNjQI HNW eZQHj MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B10 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs